Voices of Emancipation : Understanding Slavery, the Civil War, and Reconstruction through the U.S. Pension Bureau Files. - Regosin, Elizabeth A. (NYU Press, 2008)
Voices of Emancipation seeks to recover the lives and words of former slaves in vivid detail, mining the case files of the U.S. Pension Bureau, which administered a huge pension system for Union veterans and their survivors in the decades following the Civil War. The files contain an invaluable, first-hand perspective of slavery, emancipation, black military service, and freedom. Moreover, as Pension Bureau examiners began interviewing black Union veterans and their families shortly after the Civil War, the files are arguably among the earliest sources of ex-slaves reflecting on their lives, o.